Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $\{t_i\}_{i=1}^n$ be a partition of $[0,t]$ and $W$ a standard Brownian motion. Write $W_i$ for $W_{t_i}$.
Show $$ \lim \sum W_{i} (W_{i+1}-W_i)=\frac12 W^2_t-\frac12 t $$ where the limit is in probability.

The proof is in our textbook (Kurtz, Stochastic Analysis). It goes as follow \begin{align} \lim \sum_{i=1}^n W_{i} (W_{i+1}-W_i) &= \lim \sum_{i=1}^n \left( W_i W_{i+1} - \frac12 W^2_{i+1}-\frac12 W^2_i \right)+\sum_{i=1}^n \left( \frac12 W^2_{i+1} - \frac12 W^2_i \right) \\ &=\frac12 W_t^2 - \lim \frac12 \sum_{i=1}^n \left( W_{i+1}-W_{i} \right)^2 \\ &=\frac12 W_t^2 - \frac12 t^2 \end{align}

How does the second equality follows?

share|cite|improve this question
Could you add parenthesis to the last sum, and bounds of summation, if possible. It is ambiguous as written. – Sasha Oct 9 '12 at 16:05
@Sasha your comment mad me realize I didn't grasp the book argument. I added the complete argument plus the edits ou suggest. Thank you. – Nicolas Essis-Breton Oct 9 '12 at 16:27
up vote 4 down vote accepted

The second sum in the RHS of the first equality is telescopic and gives the first term in the second line. For the first sum, note that $$W_iW_{i+1}-\frac 12W_{i+1}^2-\frac 12W_i^2=-\frac 12(W_{i+1}-W_i)^2,$$ hence a factor $\frac 12$ is missing.

share|cite|improve this answer

Usually, for a Riemann integral, you say $$ \int f(t) dt = \lim_{|\delta t| \to 0} \sum f(t) \Delta t $$

Your textbook is showing that $\Delta W = W_{i+1}- W_i \approx \sqrt{\Delta t}$ since variance of random walk grows as the square-root of time.

First of all there's a telescoping sum: $$ \sum_{i=1}^n \left( \frac12 W^2_{i+1} - \frac12 W^2_i \right) = \frac12 W_t^2 $$

and then binomial formula $(x+y)^2 = x^2 + 2xy + y^2$:

$$ \lim \sum_{i=1}^n \left( W_i W_{i+1} - \frac12 W^2_{i+1}-\frac12 W^2_i \right) = \lim \sum_{i=1}^n \left( W_{i+1}-W_{i} \right)^2 = \frac12 t^2 $$

The word "lim" is very important. We can approximate the random walk over small time interval as binomial random variable $$ \mathbb{P}(\Delta W = \sqrt{\Delta t} )= \mathbb{P}(\Delta W = -\sqrt{\Delta t} )= \frac{1}{2}$$ and no matter what $(\Delta W)^2 = \Delta t$.

share|cite|improve this answer
In your display after "binomial formula", a factor of 1/2 is missing. – Nate Eldredge Oct 9 '12 at 16:57

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.